Pengaruh Gaya Hidup Pegawai Dinas Pendidikan Provinsi Riau Terhadap Citra Diri Dalam Menjalankan Tugas Dan Fungsinya - Syahkila, Syahkila; Indrawati, Indrawati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The quality of the employees can determine the lifestyle and self-image of employees themselves and tendencies can change influenced by the dominant factors. This research was conducted at the Riau Province Education Office. This study aimed to determine Employee Lifestyle's effect on Self Image in carrying out their Duties and Functions. Sampling using the census method was as many as 28 people. The results of simple linear regression obtained Cronbach's Alpha values of Lifestyle Variable (X) and Self-Image of 0.915 and 0.839. Test_t results obtained t_count value 4.50 > t_table 2.048 it can be concluded that the Lifestyle variable has a positive and significant effect on employee self-image in carrying out its duties and functions. The influence of lifestyle contributes 71.1% to employee self-image in carrying out their responsibilities and functions, while the remaining 28.9% is influenced by other factors. The closeness of the relationship between lifestyle variables and employee self-image variables in carrying out their duties and functions with an R-value of 0.843 (very close).